2023
DOI: 10.1088/1361-651x/acea3c
|View full text |Cite
|
Sign up to set email alerts
|

Atomic simulation for the effect of nano-cutting parameters on the 3D surface morphology of polycrystalline γ-TiAl alloy

Abstract: γ-TiAl alloy is one of the most potentially lightweight and high-temperature structural materials, and its machined surface quality has a significant effect on member service performance. Despite the extensive research on plastic removal and defect evolution under different cutting parameters, the forming mechanism of surface topography is not perfect under different cutting parameters. It is necessary to study the variation law of surface topography under the influence of different cutting parameters from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The red indicates tensile stress, and the blue presents compressive stress. The results suggest that the compressive stress of the CoCuFeNiPd HEA sample concentrates under and in front of the cutting tool because of the cutting force and pile-up of atoms [38,39]. The cutting tool goes through, leaving residual tensile stress on the machined surface due to the elastic recovery of the sample surface, as shown in figures 3(a2) and (b2).…”
Section: The Cutting Processmentioning
confidence: 93%
“…The red indicates tensile stress, and the blue presents compressive stress. The results suggest that the compressive stress of the CoCuFeNiPd HEA sample concentrates under and in front of the cutting tool because of the cutting force and pile-up of atoms [38,39]. The cutting tool goes through, leaving residual tensile stress on the machined surface due to the elastic recovery of the sample surface, as shown in figures 3(a2) and (b2).…”
Section: The Cutting Processmentioning
confidence: 93%
“…By studying chip, hydrostatic stress distribution and dislocation density, the mechanism of influence of different cutting speeds and cutting depths on surface quality and subsurface damage was described. Guo et al [17] investigated the influence of cutting depths and cutting speeds on the machined surface topography during nano-cutting of polycrystalline γ-TiAl alloys by MD. The results show that a smaller cutting depth and an appropriately higher cutting speed can effectively improve the surface quality of the polycrystalline γ-TiAl alloy, and optimize its nano-cutting process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, domestic and foreign scholars have carried out a large number of experimental studies and simulations on single and polycrystalline metal material cutting, including the study of cutting process parameters [11][12][13], tool geometry parameters [14,15], cutting temperature [16], grain boundaries [17], grain size [18][19][20] and so on. Guo et al used MD simulation to study the effect of process parameters on the cutting process of polycrystalline γ-TiAl alloy workpieces, and concluded that the average cutting force and friction coefficient increase with the increase of the depth of cut; increasing the cutting speed will induce amorphization of the material and plastic side flow, leading to a significant increase in the contour peaks on both sides of the machined surface [21]. Geng et al used MD simulation to study the effect of cutting force on atomic flow and material buildup [22].…”
Section: Introductionmentioning
confidence: 99%